Microscopia. - Deweer, Mark; Coucke, Jo (Otegem : Deweer Art Gallery, 1987)
Bach, Elvira ; Brus, Johannes ; Bunk, Holger ; Elias ; Fabre, Jan ; Höckelmann, Antonius ; Hofkunst, Alfred ; Immendorff, Jörg ; Lange, thomas ; Müller, Joseph-Felix ; Näher, Christa ; Panamarenko ; Penck, A.R. ; Vande kerckhove, Hans ; Winters, Robin
Microscopia, Deweer Art Gallery, Otegem (Zwevegem), 9.5 - 6.6.87
Nederlands & Frans
kunstcatalogus